Metode Blended Learning pada Pelatihan Keperawatan - Azizah, Yuni; Hariyati, Rr. Tutik Sri; Afriani, Tuti; Pujasari, Hening (Journal of Telenursing (JOTING), 2024)
This study aims to see the effect of blended learning based on a literature review. The research method used in this study is using a systematic review method. Articles are taken from the EBSCOHost, ScienceDirect, and PubMed databases. Articles are collected using the following keywords: nursing competencies, nurse competencies, and blended learning. Eight articles have been selected and critically reviewed using the Joanna Briggs Institute (JBI) critical review guidelines. The results of this study indicate that blended learning can be an effective approach to improving various outcomes in nursing education and training, such as clinical skill competencies self-efficacy, attitude, knowledge, decision-making, critical thinking, motivation, satisfaction with learning, self-confidence of training participants. This study concludes that the blended learning method is effective for nurse education and training. Keywords: Blended Learning, Nurse Training, Nursing Education, Nurses